Kitab tib ilmu perubatan Melayu (Kuala Lumpur Perpustakaan Negara Malaysia Kementerian Kebudayaan, Kesenian, dan Warisan Malaysia, 2006)
Traditional medicine in Malay manuscripts in the collection of Perpustakaan Negara Malaysia; research.
Includes bibliographical references (p. 394-397) and index.